2021
DOI: 10.34172/joddd.2021.037
|View full text |Cite
|
Sign up to set email alerts
|

Stability of dental implants with sandblasted and acid-etched (SLA) and modified (SLActive) surfaces during the osseointegration period

Abstract: Background. The surface properties of implants are effective factors for increasing the osseointegration and activity of osteoprogenitor cells. This study compared the stability of dental implants with sandblasted and acid-etched (SLA) and modified surfaces (SLActive) using the resonance frequency analysis (RFA). Methods. In a split-mouth design, 50 dental implants with either SLA surface properties (n=25) or modified (SLActive) surface properties (n=25) were placed in the mandibles of 12 patients with a bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Consequently, many authors understood the importance of removing these hydrocarbon deposits, or preventing their onset prior to implant placement, without affecting surface topography and hydrophilicity [10,18,31]. One of the methods developed to counter the implant-aging process is a chemically modified SLA surface, SLActive (SLActive, Institute Straumann AG, Basel, CH, Switzerland), where implants are conserved in nitrogen in a sealed glass tube with an isotonic NaCl solution to avoid air contact and drying and maintain a clean TiO 2 layer, preserving surface hydrophilicity and promoting osseointegration [32]. This modification in surface treatment and storage was shown to increase the bone apposition rate and BIC at the early healing stages when compared to the non-modified SLA surface [33].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, many authors understood the importance of removing these hydrocarbon deposits, or preventing their onset prior to implant placement, without affecting surface topography and hydrophilicity [10,18,31]. One of the methods developed to counter the implant-aging process is a chemically modified SLA surface, SLActive (SLActive, Institute Straumann AG, Basel, CH, Switzerland), where implants are conserved in nitrogen in a sealed glass tube with an isotonic NaCl solution to avoid air contact and drying and maintain a clean TiO 2 layer, preserving surface hydrophilicity and promoting osseointegration [32]. This modification in surface treatment and storage was shown to increase the bone apposition rate and BIC at the early healing stages when compared to the non-modified SLA surface [33].…”
Section: Discussionmentioning
confidence: 99%
“…This surface is considered in the present work as a negative control. SLA surfaces have shown enhanced results over machined and seem to yield promising results, with higher success rates and faster loading time even in soft bone [ 18 , 19 , 73 ]. SLA was used as positive control.…”
Section: Discussionmentioning
confidence: 99%
“…In choosing the most suitable implant for maxillary molar immediate implant, tapered SLA implant is most reliable. Previous studies demonstrated the superiority of tapered SLA in achieving primary and secondary stability compared with other types of implants due to its advantageous properties in improving osteoblast differentiation; producing osteogenic factors, growth factors, and cytokines; and increasing bone-implant contact 30 - 32 . Tapered SLA dental implants such as Straumann, Shinhung Implant System, and Anyone by Megagen also provide self-cutting effects, which are favorable in preserving crestal bone level especially in immediate implant placement 33 .…”
Section: Discussionmentioning
confidence: 99%